K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 8 2015

\(M=x^2+y^2-4x-4y+2xy+100=\left(x^2+2xy+y^2\right)-\left(4x+4y\right)+100\)

       \(=\left(x+y\right)^2-4\left(x+y\right)+100=3^2-4\cdot3+100=97\)

Vậy \(M=97\)

20 tháng 8 2018

+) ta có : \(D=x^2+y^2+2xy-4x-4y+100\)

\(=\left(x+y\right)^2-4\left(x+y\right)+100=3^2-4.3+100=97\)

+) ta có : \(2x^2+y^2=4y-4x-6\Leftrightarrow2x^2+4x+2+y^2-4y+4=0\)

\(\Leftrightarrow2\left(x+1\right)^2+\left(y-2\right)^2=0\Leftrightarrow\left\{{}\begin{matrix}x=-1\\y=2\end{matrix}\right.\)

thế vào \(A\) ta có :

\(A=\dfrac{2x^{100}+5\left(y-3\right)^{2011}}{x+y}=\dfrac{2.\left(-1\right)^{100}+5\left(2-3\right)^{2011}}{-1+2}=-3\)

9 tháng 7 2018

a)  \(A=x^2+2xy+y^2-4x-4y+1\)

\(=\left(x+y\right)^2-4\left(x+y\right)+1\)

\(=3^2-4.3+1=-2\)

b)  \(B=x\left(x+2\right)+y\left(y-2\right)-2xy+37\)

\(=x^2+2x+y^2-2y-2xy+37\)

\(=\left(x-y\right)^2+2\left(x-y\right)+37\)

\(=7^2+2.7+37=100\)

c)  \(C=x^2+4y^2-2x+10+4xy-4y\)

\(=\left(x+2y\right)^2-2\left(x+2y\right)+10\)

\(=5^2-2.5+10=25\)

9 tháng 7 2018

a) \(A=x^2+2xy+y^2-4x-4v+1\)

\(=\left(x+y\right)^2-4\left(x+y\right)+1\)

\(=3^2-4.3+1=-2\)

15 tháng 7 2015

 

A=x2+2xy+y2-4x-4y+1

 =(x+y)2-4.(x+y)+1

thay x+1= 3 ta được:

A=32-4.3+1

=9-12+1

=-2

15 tháng 7 2015

Dễ ợt! 

A= X2 +2XY+Y2-4X-4Y+1=(X+Y) 2 -4(X+Y)+1=32-4*3+1=9-12+1=-2

2 tháng 7 2016

\(A=x^2+2xy+y^2-4x-4y+1\)

\(=\left(x+y\right)^2-4\left(x+y\right)+1=3^2-4.3+1=-2\)

Vậy A=-2

8 tháng 9 2016

DÀI THẾ AI LÀM NỔI